Adaptation of the online moral disengagement scale to the Turkish population and its association with empathic tendency and cyberbullying - Fuad Bakioğlu; Bahtiyar Eraslan Çapan; Sami Kırteke; Amir H Pakpour (BMC Psychology)
Abstract Background Traditional moral disengagement is observed in daily life. However, with the increase in time spent in virtual environments, the need to also investigate online moral disengagement (OMD) is evident. In this study, we aimed to adapt the OMD Scale (OMDS) to the Turkish population and examine the relationship among OMD, empathic tendency, and cyberbullying. Methods A total of 694 volunteering Turkish adolescents, 404 (58.2%) females and 290 (41.8%) males and with a mean age of 15.19 years (range: 14–17 years; standard deviation = 1.09), were included. Data were collected using the OMDS, Cyberbullying Scale, and Adolescent KA-Sİ Empathic Tendency Scale. The study was conducted in several stages: confirmatory factor analysis (CFA), item factor loading, item-total correlation, concurrent analysis, mediating analysis, and reliability analysis. Results The CFA confirmed the validity of the eight-item structure OMDS. The findings also revealed a significant relationship between OMD, empathic tendency, and cyberbullying. Precisely, OMD mediated the relationship between empathic tendency and cyberbullying. Conclusion The reliability values of the OMDS were good. Likewise, the Turkish version of the scale was also valid and reliable. OMD mediated the relationship between empathic tendency and cyberbullying.